Perilaku Keuangan Menabung Mahasiswa Rantau Fakultas Ekonomi dan Bisnis UPN “Veteran” Jawa Timur - Astimeyra, Dhea Nanda; Nur, Dhani Ichsanuddin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The ability to manage finances effectively is crucial for students living away from home, as they must manage their own budgets while meeting various academic and personal needs. This study aims to analyze the relationship between financial literacy, lifestyle, and financial attitudes toward saving behavior among students of the Faculty of Economics and Business at UPN "Veteran" Jawa Timur who live away from home. The research employs a quantitative approach with variable measurement using a Likert scale. The sampling technique used is purposive sampling, involving 98 respondents. Hypotheses were tested using SmartPLS software. The results show that financial literacy contributes to saving behavior decisions among students of the Faculty of Economics and Business at UPN "Veteran" Jawa Timur, lifestyle contributes to saving behavior decisions, and financial attitudes also contribute to saving behavior decisions among these students.